2004
DOI: 10.1056/nejmoa042135
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity as Compared with Physical Activity in Predicting Mortality among Women

Abstract: Both increased adiposity and reduced physical activity are strong and independent predictors of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
221
4
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 682 publications
(244 citation statements)
references
References 27 publications
10
221
4
9
Order By: Relevance
“…L'inactivité physique et l'adiposité constituaient toutes deux d'importants détermi-nants de la mortalité, même si la contribution indépendante de l'adiposité était difficile à évaluer à cause du nombre plus élevé de covariables utilisées dans la plupart des analyses. La plupart des études récentes indiquent néanmoins que l'inactivité physique et l'obésité sont des prédicteurs indé-pendants de la mortalité (Hu et al 2004;Katzmarzyk et Craig 2006). Katzmarzyk et Craig (2006) ont constaté que l'activité physique demeurait un prédicteur indépendant de la mortalité à 12 ans chez les femmes canadiennes de 20 à 69 ans, même lorsqu'on a inclus le tour de taille dans le modèle de prédiction.…”
Section: Figunclassified
“…L'inactivité physique et l'adiposité constituaient toutes deux d'importants détermi-nants de la mortalité, même si la contribution indépendante de l'adiposité était difficile à évaluer à cause du nombre plus élevé de covariables utilisées dans la plupart des analyses. La plupart des études récentes indiquent néanmoins que l'inactivité physique et l'obésité sont des prédicteurs indé-pendants de la mortalité (Hu et al 2004;Katzmarzyk et Craig 2006). Katzmarzyk et Craig (2006) ont constaté que l'activité physique demeurait un prédicteur indépendant de la mortalité à 12 ans chez les femmes canadiennes de 20 à 69 ans, même lorsqu'on a inclus le tour de taille dans le modèle de prédiction.…”
Section: Figunclassified
“…For other cancers, the association is less clear 1, 2. An inverse association is also observed between physical activity and cancer mortality, for total cancer 3, 4, 5, 6, 7, 8, 9 and cancer‐specific for colon, liver, and lung cancer 3, 6, 9, 10. Whether prediagnostic physical activity influences cancer survival in cancer patients is a question given less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from different countries with different lifestyles have shown consistently that obesity is associated with an increased risk of all-cause mortality. A near linear relationship between body mass index (BMI) and mortality was usually observed in men and women with a BMI of 30 kg/m 2 and more [2][3][4][5][6][7][8][9][10][11][12]. Some of the large cohort studies like the Nurses Health Study [3], the Cancer Prevention Study II [4] or the Korean Cancer Prevention Study [11] were able to perform analyses stratified by the cause of death.…”
Section: Introductionmentioning
confidence: 99%